Effects of drying process on total phenolics, antioxidant activity and flavonoid contents of common Mediterranean herbs - Rababah, Taha M.; Al-u'datt, Muhammad; Alhamad, Mohammad; Al-Mahasneh, Majdi; Ereifej, Khalil; Andrade, Juan; Altarifi, Bayan; Almajwal, Ali; Yang, Wade (International Journal of Agricultural and Biological Engineering, 2015)
Four different fresh and dried herb species (sage, thyme, mint and lemonbalm) were evaluated to study the effect of drying process on the total phenolics, antioxidant activity, flavonoid contents and color properties. Fresh mint had the highest contents of total phenolics (335.4 mg GAE/100 g), whereas lower levels were respectively found in sage (316.4 mg GAE/100 g) followed by lemonbalm (303.2 mg GAE/100 g) and thyme (299.2 mg GAE/100 g). Dry processing significantly decreased the phytochemical contents of all investigated herbs. Compare to air drying, total phenolics, antioxidant activity and flavonoids content in herbs decreased apparently by oven dried. Fresh mint had the highest antioxidant activity (87.46%) and flavonoids content (298.51 mg CE/100 g), while the fresh sage, thyme and lemonbalm were found to have antioxidant activity values of 86.81%, 86.56% and 85.26%, respectively. Results showed that air drying herbs contained more total phenolics, antioxidant activity, and flavonoids than oven drying herbs. Keywords: herbs, drying process, antioxidant activity, flavonoids DOI: 10.3965/j.ijabe.20150802.1496